Dinamika Minoritas Muslim di Amerika Serikat - Kartini, Indriana (Pusat Penelitian Politik, 2005)
The September 11, 2001 attacks against the United States has become the tragedy for American society, including muslim minority in America. In the days following September 11, many people in America points afinger at a Muslim terror suspect. Muslims and people from various ethnic who appeared to be of Middle Eastern decent become the victims of discrimination and harrasment. The tragedy of September ll'h, has become the turning point for Bush administration to conduct atough policy in order to fight terrorism. President George W. Bush has dramatically overreacted to the September 11 attacks. It is bitterly ironic that it was Bush â€™s statements condemning â€œsecret evidence â€ policy and profiling that earned him the endorsement ofthe Muslim-American block vote in the last elections in the year 2000. However, today Bush administration expand these practices by conducting the USA PATRIOT Act with reckless abandon. The purpose ofthis research was to explore the problems faced by Muslim related to their position as minority in America and how they response to their problems.